USING PEER-RESPONSES AND TEACHER’S WRITTEN FEEDBACK TECHNIQUE THROUGH BLOG IN WRITING II CLASS OF ENGLISH EDUCATION STUDY PROGRAM - Annisa Astrid (Vision: Journal for Language and Foreign Language Learning, 2015)
This article discusses the result of the research undertaken at PBI UIN Raden Fatah Palembang. The sample of the research was 60 students in Writing II Classes. This study included a guided writing instruction and a questionnaire survey.There were two groups of students involved in this study; control and experimental group. Students in the control group were taught using Peer Response Technique, and the experimental one by using Teacher’s written feedback technique. Both groups employed online Blog writing as the means to share feedback. After the treatment done, the students were required to fi ll the questionnaire items in order to assess their attitude toward the use of Blog in their writing class. The results of the research showed that; (1) there was not a signifi cant difference between students writing achievement before being taught with Teacher’s Written Feedback Technique and after being taught with that technique (2) there was a signifi cant difference between students’ writing achievement before being taught by using Peer Response Technique and after being taught by using that technique (3) there was signifi cant difference between students’ writing achievement who were taught by using Peer Response Technique than those who were taught by using Teachers’ Written Feedback and (4) there was positive attitude toward the process of teaching and learning Writing by Using Blog Writing.